Aeroallergen sensitization predominates in children with atopic dermatitis - H M Thilanka Seneviratne; K M K. Somaratne; Subhani Brabaharan; G Dilan Dileepa Jayarathne Bandara; A R. T Vindya Alahakoon; Priyanka Senevivikrama; P V Rangith Kumarasiri (Wolters Kluwer Medknow Publications, 2022)
Background: Children with atopic dermatitis (AD) suffer from frequent flare-ups. Correct identification of allergens responsible for flare-ups is important in managing AD. Suspecting food allergens as culprits may result in unnecessary food restrictions which adversely affect the growth of these children. In view of this fact, we aimed to assess the allergen sensitization pattern of children with AD in Sri Lanka. Objective: The objective is to assess the food and aeroallergen sensitization pattern of children with AD. Materials and Methods: This study was conducted among 100 consecutive patients refereed to the dermatology clinics of a specialized children's hospital and a tertiary care hospital with the clinical diagnosis of AD. Age ranged from 1 to 18 years. All underwent a Skin prick test (SPT), using prick test solutions for house dust mite Dermatophagoids pteronyssinus (HDM-DP), Aspergillus fumigatus (AF), cat epithelia (CE), cow's milk (CM), egg white (EW), and peanut. Results: Of 100 patients 53.0% had positive SPT for HDM-DP. 15.0% were positive for CE, 9.0% positive for AF. All above three are aeroallergens, food allergen sensitivities were 9.0% for CM, 2.0% for EW, and 1.0% for peanuts. It is of note that the wheal size of HDM-DP SPT showed a very strong correlation with the age of the subject (R2 = 0.0723, P = 0.007). Conclusion: Aeroallergen sensitization predominate over food allergen sensitization in children with AD. HDM and CE were the most common aeroallergen sensitivities. The wheal size of HDM-DP had a very strong positive correlation with age.